2010
DOI: 10.1111/j.1551-2916.2010.04259.x
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Transport Property of Copper site Doped La2CuO4

Abstract: The transport properties of p‐type polycrystalline La2Cu1−xMxO4 (MCo and Mn) have been investigated in the high temperature domain above room temperature up to 973 K. The electrical resistivity of La2Cu1−xMxO4 undergoes a temperature driven semiconducting (insulating) to metallic transition at high temperature (∼750 K) and a doping induced metal to semiconductor transition at room temperature. The Arrhenius plot of the ln(ρ/T)∼1/T shows a conducting mechanism and in the La2Cu1−xMxO4 (M:Co and Mn) a transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…[18] In addition, by doping Co and Mn at Cu site using a two-step chemical method, Xu et al found two physical changes in resistivity with temperature and doping concen-tration, and the electrical transport properties could be further optimized by controlling the doping content on Cu site and adjusting the oxygen vacancy. [19] However, the thermoelectric performance of La 2 CuO 4 is still relatively lower, a further optimization is needed.…”
Section: Introductionmentioning
confidence: 99%
“…[18] In addition, by doping Co and Mn at Cu site using a two-step chemical method, Xu et al found two physical changes in resistivity with temperature and doping concen-tration, and the electrical transport properties could be further optimized by controlling the doping content on Cu site and adjusting the oxygen vacancy. [19] However, the thermoelectric performance of La 2 CuO 4 is still relatively lower, a further optimization is needed.…”
Section: Introductionmentioning
confidence: 99%